The dilemma of delegating search: Budgeting in public employment services - John T. Addison; Martin Altemeyer-Bartscher; Thomas Kuhn (Institute for the Study of Labor (IZA), 2010)
The poor performance often attributed to many public employment services may be explained in part by a delegation problem between the central office and local job centers. In markets characterized by frictions, job centers function as match-makers, linking job seekers with relevant vacancies. Because their search intensity in contacting employers and collecting data is not verifiable by the central authority, a typical moral hazard problem can arise. To overcome the delegation problem and provide high-powered incentives for high levels of search effort on the part of job centers, we propose output-related schemes that assign greater staff capacity to agencies achieving high strike rates.
Keywords: J64; D82; 330; matching unemployment; public employment service; delegation problem; moral hazard; search theory; Arbeitsvermittlung; Arbeitsverwaltung; Moral Hazard; Arbeitsuche; Kooperative Führung; Betriebliche Budgetierung; Ökonomischer Anreiz; Theorie